2012
DOI: 10.1258/mi.2011.011111
|View full text |Cite
|
Sign up to set email alerts
|

Postmenopausal vaginal bleeding in women using hormone replacement therapy

Abstract: Postmenopausal women presenting with vaginal bleeding and using combined HRT preparations have significantly lower risk of being diagnosed with endometrial cancer when compared with women not using HRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…16,17 Even though, PMB is commonly associated with endometrial polyps or/and might result from spontaneous bleeding in women treating with hormone therapy. 18 In some studies, the risks of developing endometrial cancer in females with post menopausal bleeding vary widely from 3% to 25%. 19,20 Most endometrial cancer is diagnosed at a localized stage and is usually treatable with surgery, with a -year survival rate of about 95%.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Even though, PMB is commonly associated with endometrial polyps or/and might result from spontaneous bleeding in women treating with hormone therapy. 18 In some studies, the risks of developing endometrial cancer in females with post menopausal bleeding vary widely from 3% to 25%. 19,20 Most endometrial cancer is diagnosed at a localized stage and is usually treatable with surgery, with a -year survival rate of about 95%.…”
Section: Introductionmentioning
confidence: 99%
“…14 In women on HRT, this risk is lower as reported in previous studies. In a study by Burbos et al., 3 4847 post-menopausal women with bleeding were investigated with an endometrial biopsy, including 750 (15%) women on HRT. The study found that women using HRT preparations were significantly less likely to be diagnosed with endometrial cancer (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…1 Sequential HRT (seq-HRT) gives up to 90% of women a cyclical bleed whereas women on continuous combined HRT (con-HRT) preparations are expected to be amenorrhoeic due to endometrial atrophy. 2,3 Unscheduled bleeding is defined as abnormal bleeding on seq- or con-HRT six months post initiation of therapy or after a period of amenorrhoea. 4 An initial phase of irregular bleeding is common in women in the first six months of treatment 2 while persistent bleeding after this period of treatment should always be investigated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations